Pengaruh Pelatihan Kerja Dan Motivasi Kepada Karyawan Untuk Meningkatkan Etos Kerja Selama Masa Pandemic Covid-19 Upt Puskemas Karanganyar Di Kabupaten Karanganyar - Stela Rahma Marisa; Johnson Dongoran (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
Work training and motivation are very useful for every employee and company, what's more, it will produce a good work ethic for each individual. The purpose of this study was to a) examine the effect of job training on work ethic during the Covid-19 pandemic at UPT Puskesmas Karanganyar, Karanganyar Regency. b) Testing the effect of motivation on work ethic during the Covid-19 Pandemic at UPT Puskesmas Karanganyar, Karanganyar Regency. The research method used in this study is through the distribution of questionnaires, the methods used in this study are validity and reliability tests, classical assumption tests and multiple linear regression tests. The number of samples in this study was 57 employees of UPT Puskesmas Karanganyar. This study shows the results that job training has a positive effect on work ethic at UPT Puskemas Karanganyar, work motivation has a positive effect on work ethic at UPT Puskemas Karanganyar. Keywords : Work Training, Motivation, Work Ethos